Hands-On Software Architecture with C# 8 and .NET Core 3 : Architecting software solutions using microservices, DevOps, and design patterns for Azure Cloud /: Architecting software solutions using microservices, DevOps, and design patterns for Azure Cloud. (2019) - Baptista, Gabriel; Abbruzzese, Francesco
No abstract available